2020
DOI: 10.1080/00220388.2020.1736282
|View full text |Cite
|
Sign up to set email alerts
|

Rural Roads, Poverty, and Resilience: Evidence from Ethiopia

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 34 publications
(35 reference statements)
0
30
0
Order By: Relevance
“…As contributors to improved mobility for large populations within rural and isolated areas, rural roads directly support the poorest members of communities, who are at a "transport disadvantage" and frequently miss out on the benefits of larger and more major transportation infrastructure due to proximity or financial constraints [7,207,209,222]. Therefore, some authors have suggested that rural roads yield greater contributions to social welfare than higher-level and more engineered roads, and can be described as a "pro-poor" intervention [8,51,207,227]. Recent review papers acknowledge that rural roads can be more effective in reducing poverty than roads of higher standards, and may reduce poverty up to three times more per unit of investment than tarmac roads [7,8].…”
Section: Rural Roadsmentioning
confidence: 99%
See 1 more Smart Citation
“…As contributors to improved mobility for large populations within rural and isolated areas, rural roads directly support the poorest members of communities, who are at a "transport disadvantage" and frequently miss out on the benefits of larger and more major transportation infrastructure due to proximity or financial constraints [7,207,209,222]. Therefore, some authors have suggested that rural roads yield greater contributions to social welfare than higher-level and more engineered roads, and can be described as a "pro-poor" intervention [8,51,207,227]. Recent review papers acknowledge that rural roads can be more effective in reducing poverty than roads of higher standards, and may reduce poverty up to three times more per unit of investment than tarmac roads [7,8].…”
Section: Rural Roadsmentioning
confidence: 99%
“…Recent review papers acknowledge that rural roads can be more effective in reducing poverty than roads of higher standards, and may reduce poverty up to three times more per unit of investment than tarmac roads [7,8]. Specifically, rural roads support an increase in living standards by providing stimulus to poor areas that are reliant upon agriculture-based economics [216,227]. Focusing on the first and last mile of communities, rural roads help to decrease costs of transportation between rural villages and markets, supporting both agricultural production and market activity [8,218,227].…”
Section: Rural Roadsmentioning
confidence: 99%
“…Minimizing poverty and narrowing the income inequality gap are a priority for both nations and international communities (Rankin, 2013;Zhang et al, 2015). Technology adoption, infrastructure construction, aid, and other factors are expected to help alleviate poverty in developing countries (Nakamura et al, 2020;Shapiro, 2019;Wossen et al, 2019). In particular, financial development in rural areas is deemed essential for poverty reduction (Imai et al, 2010;Mendola, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The large impact of market access on agricultural practices has further been confirmed by specifically designed studies in different countries in Africa ( Stifel and Minten, 2008 , Vandercasteelen et al, 2018 ). Finally, in Ethiopia, recent evidence suggest that more connected areas are less vulnerable to weather shocks ( Hill and Fuje, 2016 , Hirvonen et al, 2020 , Nakamura et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%